Lease Versus Purchase: Case Study of PT. Ardhia Multi Parama - Issadi, Alif Anandata; Nugroho, Anggoro Budi (The Indonesian Journal of Business Administration, 2015)
Abstract.This study analyze and determine which financing method for DengarSaya, a digital production company, to get a recording studio and all needed equipment regarded to the studio which are born from the needs of DengarSaya to having its own recording studio for its main core value creation. DengarSaya itself is a digital production company which offers and provides services to make digital products concentrated in music, video, and graphic production. The target customer is every person or institution that needs digital products. However, as an early established SME, DengarSaya wants to gain recording studio with the most efficient financing method. Meanwhile, purchase the asset by cash is seems not attractive for DengarSaya since its financial situation it has. In order resolve the problem, this study use collecting data, literature comparative study, financing method calculation and evaluation, decision making technique, difference between financing scheme, also sensitivity analysis to determine which financing method fit best for DengarSaya. These method and technique will give overview about the condition of DengarSaya, the situation in the related industry, and which financing method is the most attractive for DengarSaya; to lease or to purchase by cash and absorbed the risks on their own which can be mitigated by insurance premium. This study resulting in leasing as the most attractive financing method for DengarSaya, explained in narrative form. It also resulting an implementation plan and which financing scheme fit best is selected as a picture of the most possible and a recommendation to the company for use as a reference in determining and providing the tangible asset needed.Keywords: DengarSaya, finance, leasing, purchase by cash, financing method, SME, NAL (Net Advantage to Leasing), Sensitivity analysis, Decision Tree, PV cost, digital production.Â Â